Repercussions of chronic kidney failure on the biopsychosocial context of patients in hemodialytic treatment - Ferreira, Ricardo Bruno Santos (2022)
Introduction: chronic renal failure is considered an important public health problem since both the disease and the treatment have profound impacts on the entire life context of the affected person. Objective: to understand the repercussions of chronic renal failure in the biopsychosocial context of patients undergoing hemodialysis. Methodology: this is a descriptive, qualitative study developed in a regional reference hospital for the treatment of hemodialysis in the State of Bahia, Brazil. Twenty people with chronic renal failure undergoing hemodialysis took part in the study; all of them were over 18 years old. The data collection was carried out in December 2019 through a semi-structured interview. Subsequently, the data were systematized through Content Analysis. Results: the study showed that renal failure brings multidimensional repercussions to the patients due to the difficulties in entering the world market, difficulties related to food and water restrictions, limitations related to leisure and the physical activity practices, and the impact on sexuality. However, despite the limitations caused by the disease, patients showed themselves resilient in highlighting the importance of the treatment to guarantee their quality of life. Conclusion: the study points to the need of building specific policies aimed at reducing the impact caused by chronic renal failure since it is a chronic and irreversible disease that requires permanent treatment. Furthermore, the findings confirm the need for individualized assessment and the provision of holistic and humanized care by health professionals as a way to minimize the impact of the illness.